A field investigation of physical workloads imposed on harvesters in South African forestry - Christie, Candice Jo-Anne (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2006)
The focus of this field investigation was an analysis of the work demands being placed on South African forestry workers, in particular Chainsaw Operators and Stackers. Working postures, physiological and perceptual responses were assessed on a sample of 58 workers (29 Chainsaw Operators and 29 Stackers) during a 'normal' working shift. Body mass was measured before and after work in order to determine dehydration levels. Polar heart rate monitors were fitted to six workers each day over a period of two weeks in order to record 'working' heart rates. Fluid and food intake was monitored and recorded during this initial data collection phase. The Rating of Perceived Exertion and Body Discomfort Scales were explained in Zulu, their native language, and workers were asked to rate their perceptions of effort at regular intervals during work, while areas and intensity of body discomfort was obtained on completion of work. After completing a work shift, a 30 minute 'recovery' period was given, thereafter a portable ergospirometer, the k4bÂ², was attached to the worker who then participated in a progressive, submaximal step test for the purpose of establishing individual, and group, heart rate-oxygen uptake (HR/VO[subscript 2]) regressions for predicting oxygen uptake from 'working' heart rate responses. These procedures were repeated four weeks later following the introduction of a fluid and nutritional supplement during work which was delivered to the workers while they were executing their tasks. The results revealed awkward working postures with a predominance of trunk flexion during all the harvesting tasks; these postures, adopted for long periods during work, are very likely to lead to the development of musculoskeletal injuries. The mean working heart rates were 123.3 bt.min[superscript (-1)] and 117.6 bt.min[superscript (-1)] during chainsaw operations and stacking respectively. During the step test, the mean heart rate and oxygen uptake responses were 127.9 bt.min[superscript (-1)] and 22.9 mlO[subscript 2].kg[superscript (-1)].min[superscript (-1)] (Chainsaw Operators) and 116.9 bt.min[superscript (-1)] and 24.0 mlO[subscript 2].kg[superscript (-1)].min[superscript (-1)] (Stackers), revealing no significant difference between the 'working' heart rates and the heart rates recorded during the step test. Physiological responses were analyzed over the full work shift which was divided into four quarters. Heart rate and oxygen uptake were significantly higher during the last half of the Chainsaw Operators' work shift compared to the first half. Heart rate increased from 120.7 bt.min[superscript (-1)] during the first quarter to 127.4 bt.min[superscript (-1)] during the last quarter of chainsaw operations. Likewise, oxygen uptake increased from 19.9 mlO[subscript 2].kg[superscript (-1)].min[superscript (-1)] to 22.9 mlO[subscript 2].kg[superscript (-1)].min[superscript (-1)] from the first to the last quarter of work. During stacking the heart rate (mean of 117.6 bt.min[superscript (-1)]) and oxygen uptake (mean of 24.6 ml.kg[superscript (-1)].min[superscript (-1)]) responses remained stable over the duration of the working shift. Workers lost, on average, 2.8% body mass during work while felling and cross-cutting and 3.6% during stacking. This reduced significantly to a loss of 0.4% body mass when re-tested following the introduction of water and food during the work period. Likewise, the energy deficit was significantly improved due to the introduction of a nutritional supplement. Pre-intervention the deficit was 8861.8 kJ (Chainsaw Operators) and 8804.2 kJ (Stackers) while in the post-intervention phase this deficit was reduced by approximately 50% for both groups of workers.
Keywords: Forests and forestry -- South Africa; Employees -- Workload; Forest products industry -- South Africa; Work -- Physiological aspects; Heart rate monitoring; Foresters -- South Africa -- Workload; Oxygen -- Physiological transport